Iron restriction inside macrophages regulates pulmonary host defense against Rhizopus species. Issue 1 (December 2018) - Andrianaki, Angeliki; Kyrmizi, Irene; Thanopoulou, Kalliopi; Baldin, Clara; Drakos, Elias; Soliman, Sameh; Shetty, Amol; McCracken, Carrie; Akoumianaki, Tonia; Stylianou, Kostas; Ioannou, Petros; Pontikoglou, Charalampos; et al.
Abstract Mucormycosis is a life-threatening respiratory fungal infection predominantly caused byRhizopus species. Mucormycosis has incompletely understood pathogenesis, particularly how abnormalities in iron metabolism compromise immune responses. Here we show how, as opposed to other filamentous fungi, Rhizopus spp. establish intracellular persistence inside alveolar macrophages (AMs). Mechanistically, lack of intracellular swelling ofRhizopus conidia results in surface retention of melanin, which induces phagosome maturation arrest through inhibition of LC3-associated phagocytosis. Intracellular inhibition ofRhizopus is an important effector mechanism, as infection of immunocompetent mice with swollen conidia, which evade phagocytosis, results in acute lethality. Concordantly, AM depletion markedly increases susceptibility to mucormycosis. Host and pathogen transcriptomics, iron supplementation studies, and genetic manipulation of iron assimilation of fungal pathways demonstrate that iron restriction inside macrophages regulates immunity againstRhizopus . Our findings shed light on the pathogenetic mechanisms of mucormycosis and reveal the role of macrophage-mediated nutritional immunity against filamentous fungi. Mucormycosis is a life-threatening respiratory fungal infection that typically occurs in patients with abnormalities in iron metabolism. Here the authors show that iron restriction inside the phagosome of macrophages is an essential component of the host defense againstRhizopus, the main species causing mucormycosis.